A novel approach to prevent graphene oxide re-aggregation during the melt compounding with polymers. (23rd November 2015) - Maio, Andrea; Fucarino, Roberto; Khatibi, Reza; Rosselli, Sergio; Bruno, Maurizio; Scaffaro, Roberto
Abstract: The technology for the preparation of polymer-GO nanocomposites was investigated by studying the structure-properties relationships of two different systems, based on PA6 and EVA, fabricated by using different preparation methods, i.e. melt mixing, wet phase inversion, and the combination of the two. The morphology of nanocomposites resulted dramatically influenced by the technique adopted and showed to be the critical variable affecting the physical properties of the materials. Finally, the mechanical and dynamic-mechanical of the nanocomposites were improved by using the hybrid technique combining the two procedures.